2017
DOI: 10.1038/onc.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lyn regulates Snail family shuttling and inhibits metastasis

Abstract: The acquisition of an invasive phenotype by epithelial cells occurs through a loss of cellular adhesion and polarity, heralding a multistep process that leads to metastatic dissemination. Since its characterization in 1995, epithelial-mesenchymal transition (EMT) has been closely linked to the metastatic process. As a defining aspect of EMT, loss of cell adhesion through downregulation of E-cadherin is carried out by several transcriptional repressors; key among them the SNAI family of transcription factors. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 66 publications
1
24
1
Order By: Relevance
“…In different tumors affecting humans, aberrant expression levels of Snai1 and Snai2 may affect EMT progression, cell invasion and migration ( 44 , 45 ). Snai1 has been demonstrated to induce hepatocellular carcinoma via enhancement of cell growth ( 46 ), and to accelerate pancreatic tumor growth ( 47 ) and breast cancer development ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In different tumors affecting humans, aberrant expression levels of Snai1 and Snai2 may affect EMT progression, cell invasion and migration ( 44 , 45 ). Snai1 has been demonstrated to induce hepatocellular carcinoma via enhancement of cell growth ( 46 ), and to accelerate pancreatic tumor growth ( 47 ) and breast cancer development ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were plated at 25,000 per in 12 well plates on circular glass slides in a 12 well plate. Cells were fixed and stained as previously described 47 using antibodies against STAT3 (1:100) and AR (1:100). DAPI was used to visualize nuclei and then the pictures were taken using Zeiss LSM confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Tornillo et al reported that LynA promotes tumour cell invasion and that a high LynA/LynB isoform ratio is associated with poor prognosis of breast cancer patients 30 . Two previous studies from different groups showed that Lyn mediates EMT 28,29 . Although the authors of these two studies did not mention which contributes to the induction of EMT (whether LynA or LynB), at least one study showed results suggesting that the overexpression of LynA induced EMT 28 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies suggested that LynA seems to contribute to the aggressive behaviour of some types of cancer [28][29][30] . Tornillo et al reported that LynA promotes tumour cell invasion and that a high LynA/LynB isoform ratio is associated with poor prognosis of breast cancer patients 30 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation